Freedom of information local government and accountability - Chapman, Richard A.; Hunt, Michael 1947- (Routledge, 2016)
Since the UK's Freedom of Information Act of 2005, which allows public right of access to information held by public authorities, considerable evidence has accumulated about the ways in which the Act has been applied in the interests of democracy. This book considers best practice regarding the operation of the Act.